1992
DOI: 10.1002/ijc.2910510603
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer in argentina. I: Risk from intake of dietary items

Abstract: A case-control study has been conducted to investigate the relationship between dietary components and risk of colon cancer in the La Plata area of Argentina. Cases are 110 patients newly diagnosed with colon cancer in 10 major hospitals between 1985 and 1986. Two neighbourhood controls per case were individually matched by age, sex and place of residence. Personal interviews elicited information on frequency of consumption of 140 food items during the 5-year period up to 6 months prior to interview. Risk is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 22 publications
1
44
1
Order By: Relevance
“…9,40,45,46 In our study, frequent consumption of dairy foods (but not high mean daily intakes) was associated with increased risk, but only in AfricanAmericans. It has been suggested that the elevated risk observed in some studies may be attributable to the fat content of dairy foods, whereas decreased risk may be due to calcium or vitamin D content.…”
Section: Discussionmentioning
confidence: 42%
“…9,40,45,46 In our study, frequent consumption of dairy foods (but not high mean daily intakes) was associated with increased risk, but only in AfricanAmericans. It has been suggested that the elevated risk observed in some studies may be attributable to the fat content of dairy foods, whereas decreased risk may be due to calcium or vitamin D content.…”
Section: Discussionmentioning
confidence: 42%
“…Two other case -control studies (Iscovich et al, 1992;Shannon et al, 1996) reported higher odds ratios for high-fat than for low-fat dairy intake, but the association was not statistically significant. An American hospital-based case -control study on patterns of milk consumption and risk of different cancers found a significant increased risk in subjects that consumed whole milk daily compared to non-consumers (Mettlin et al, 1990).…”
Section: Yoghurtmentioning
confidence: 96%
“…The ORs for the highest category of consumption vs the lowest are summarized in Figure 1. Out of 11 case -control studies, three found a significant risk increase (Benito et al, 1990;Iscovich et al, 1992;Steinmetz & Potter, 1993) and three other studies a significantly decreased risk (Shannon et al, 1996;Kampman et al, 2000;Murata et al, 1999). The diversity of dairy products may to some extent explain the inconsistencies of these results.…”
Section: Total Dairy Productsmentioning
confidence: 99%
“…Table 1 contains 30 case -control studies that had at least 99 cases and reported on meat intake (Benito et al, 1990;Bidoli et al, 1992;Centonze et al, 1994;Dales et al, 1979;Gerhardsson et al, 1991;Graham et al, 1978;Haenszel et al, 1973Haenszel et al, , 1980Hu et al, 1991;Iscovich et al, 1992;Kampman et al, 1995Kampman et al, , 1999Kato et al, 1990;Kune et al, 1987; La Vecchia (1992) 248 Italy Yes I R þ beef & pork; C-ve Centonze et al (1994) 118 Italy Yes H NS Dales et al (1979) 99 US Blacks -I N S Gerhardsson et al (1991) 559 Sweden Yes H C and R þ meats Graham et al (1978)) 586 USA (NY) -I N S Haenszel et al (1973) 179 Japanese in Hawaii -L CRC þ meat Heanszel et al (1980) 588 Japan --NS Hu et al (1991) 336 China Yes -NS Iscovich et al (1992) 110 Argentina Yes H NS Kampman et al (1995) 312 Netherlands Yes H NS Kampman et al (1999) 1542 USA Multicentre --NS Kato et al (1990) 221 Japan -I N S Kune et al (1987) 715 Australia Yes -C þ beef men, not women R þ lamb women, not men La Vecchia et al (1988) 575 N. Italy Yes -RR 2.0 CRC for meat but 3.0 for pasta þ rice La Vecchia et al (1996) 1326 N. Itlay -H CRC þ (1.6) for red meat Lee et al (1989) 203 Singapore Yes H NS Lyon et al (1988) 246 Utah, USA Yes -NS Macquart-Moulin et al (1986) 399 France Yes I NS Manousos et al (1983) 100 Greece Yes -CRC þ beef and lamb Miller et al (1983) 542 Canada Yes -R þ beef (?) Muscat et al (1994) 511 USA --NS Peters et al (1989) 146 Los Angeles, USA Yes -NS Peters et al (1992) 746 Los Angeles, USA Yes H NS Steinmetz et al (1993)…”
Section: The Case -Control Studiesmentioning
confidence: 99%